PRELIMINARY REPORT ON PALEOMAGNETIC STUDY OF ROCKS FROM THE MT. RIISER-LARSEN AREA IN ENDERBY LAND, EAST ANTARCTICA - イシカワ, ナオト; フナキ, ミノル; ISHIKAWA, Naoto; FUNAKI, Minoru (National Institute of Polar Research, 1997)
P(論文) Paleomagnetic samples were collected at eight sites from granulites of the Archean Napier Complex and dolerite dikes intruding the complex in the Mt. Riiser-Larsen area in Enderby Land, East Antarctica. Progressive demagnetization results indicate the presence of two magnetic components : the low-stability (L) and high-stability (H) components. A principal carrier of the H component is fine-grained magnetite, while the L component may be carried by coarser titanomagnetite. L components with steep negative inclination were remarkably observed in both granulite and dolerite samples. The characteristic L component is considered as a viscous remanence (VRM) in the recent geomagnetic field. A complete overprint of the VRM is observed in samples from one granulite site. The H components of two dolerite sites have positive inclinations, and their virtual geomagnetic pole positions are situated near the segment of the apparent polar wander path between 1.0 and 1.2 Ga for Australia in the East Gondwanaland frame. This may imply that the formation of East Gondwanaland can be dated back to about 1.2 Ga, if the intrusions of the dolerite dikes was related to the Amundsen dike activity in the Napier complex. The H component direction determined at one granulite site is inconsistent with other component directions, implying the possibility that the remanence might have been acquired before the intrusion of the dolerite dikes. departmental bulletin paper